2006
DOI: 10.1089/vim.2006.19.324
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of Morbillivirus Nucleoproteins

Abstract: Morbillivirus infections have been known for a long time to be associated with an acute immunosuppression in their natural hosts. Here, we show that recombinant Morbillivirus nucleoproteins from canine distemper virus, peste-des-petits-ruminants virus, and Rinderpest virus bind B-lymphocytes from dogs, goats, and cattle, respectively, similarly to measles virus nucleoprotein in humans. The use of surface plasmon resonance imaging allowed the real time detection of differential interactions between Morbilliviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Both nucleoproteins were eluted in the dead volume of the preparative SEC column (not shown). This indicates a molecular mass greater than 1300 kDa, which could correspond either to unspecific aggregates or to high degree multimers of N. Because N proteins from Paramyxoviridae members, including MeV (5) and NiV (80), are well known to form nucleocapsid-like particles when expressed in heterologous hosts, we examined the ratio between the absorbance of purified nucleoproteins at 280 and at 260 nm which gives indications on their RNA content. The A 260 /A 280 ratio for N devoid of RNA is 0.57, whereas it is Ն1.06 for the N-RNA complex containing six ribonucleotides/N monomer (see "Experimental Procedures").…”
Section: Purification Of Henipavirus N Proteins and Assessment Of Thementioning
confidence: 99%
“…Both nucleoproteins were eluted in the dead volume of the preparative SEC column (not shown). This indicates a molecular mass greater than 1300 kDa, which could correspond either to unspecific aggregates or to high degree multimers of N. Because N proteins from Paramyxoviridae members, including MeV (5) and NiV (80), are well known to form nucleocapsid-like particles when expressed in heterologous hosts, we examined the ratio between the absorbance of purified nucleoproteins at 280 and at 260 nm which gives indications on their RNA content. The A 260 /A 280 ratio for N devoid of RNA is 0.57, whereas it is Ն1.06 for the N-RNA complex containing six ribonucleotides/N monomer (see "Experimental Procedures").…”
Section: Purification Of Henipavirus N Proteins and Assessment Of Thementioning
confidence: 99%
“…Morbillivirus infections have long been known to be associated with increased immunosuppression in their natural hosts (19). DMV has been frequently reported in association with secondary infections from opportunistic bacteria or protozoa such as Toxoplasma gondii (1,7,8,11).…”
mentioning
confidence: 99%
“…Dendritic cells (DCs) are susceptible to MV infection and can transmit infection to lymphocytes. Apart from its direct effects on the immune system, MV also has indirect, longer-lasting effects on the immune system, in which the interaction between several viral proteins and the human host seems to play a role (Kerdiles et al, 2006a;Kerdiles et al, 2006b). MV-infected DCs are unable to stimulate a mixed lymphocyte reaction and can induce lymphocyte non-responsiveness through expression of MV glycoproteins.…”
Section: Induced Immune Suppressionmentioning
confidence: 99%
“…Data from several studies suggest that carriage of MV by DCs may facilitate virus spreading to secondary lymphoid organs and that MV replication in DCs may play a central role in the general immune-suppression observed during measles. Therefore, contributions of measles virus to immune-suppression are likely multifactorial and include reduced DTH responses, T lymphocyte functional deficits, altered cytokine levels, inhibition of DC function, reduced immunoglobulin production, and inhibition of IFN-γ up-regulation of MHC-II molecules (Kerdiles et al, 2006a). Leopardi et al (Leopardi et al, 1993) showed that in measles-infected monocytes, there was a 10-fold increase in the expression of MHC class II molecules.…”
Section: Induced Immune Suppressionmentioning
confidence: 99%